Cover Feature: Amine‐Borane Dehydrogenation and Transfer Hydrogenation Catalyzed by α‐Diimine Cobaltates (Chem. Eur. J. 1/2019). Issue 1 (10th December 2018) - Maier, Thomas M.; Sandl, Sebastian; Shenderovich, Ilya G.; Jacobi von Wangelin, Axel; Weigand, Jan J.; Wolf, Robert
Abstract : Highly reduced, anionic cobalt complexes supported by bis(iminoacenaphthene) diimine (BIAN) ligands catalyze the dehydrogenation of amine boranes. Using the same catalysts, transfer hydrogenations of olefins, imines, and N ‐heteroarenes with ammonia borane as a dihydrogen surrogate have been developed. Challenging trisubstituted olefins can be reduced under an external H2 pressure with ammonia borane as an activator. The cover image shows a transfer hydrogenation reaction of quinoline, an ammonia borane molecule, and the molecular structure of a precatalyst complex, where 1, 5‐cyclooctadiene serves as a placeholder for vacant coordination sites. The silhouette of the beautiful city of Regensburg, Germany, where most of this work was performed, is displayed in the background. More information can be found in the Full Paper by R. Wolf, A. Jacobi von Wangelin et al. onpage 238 .